Learning with the Show Tell Method Using Goole Slides as a Tool in the Development of Early Childhood Communcation - Dewi Mahmudah; Lilis Suryani (Universitas Muhammadiyah Enrekang, 2023)
Education in children age early focus on placement base growth and development child. Through something game one among them that is method show and tell and available media used in the learning process teach that is Google Slides. sub focus study as following : Objective implementation, planning, steps, assessment, strengths and weaknesses, barriers and solutions, impact application implementation method show and tell with Google Slides media in development communication in TK Pertiwi V Pasuruan Objective from study This intended For describe application method show and tell with Google Slides media in development ability communicate. Study This use study qualitative. Location and subject in study This consists from students in TK Pertiwi V with total 32 children. held on the moon March 2023. Research This develop language skills by using the show and tell method with Google Slide media where the teacher has the goal of improving children’s ability to communicate, either through stories or talking with their pe’rs. Impact application method show and tell with media Google Slides in development ability communication child age early that is child child become more Good in communicate.